Spaces of Change: Arab Women’s Reconfigurations of Selfhood through Heterotopias in Manal al-Sharif’s Daring to Drive (KEMANUSIAAN The Asian Journal of Humanities, 2020)
Stereotypically depicted as unresisting and passive victims of oppressive power, Saudi women are generally considered as unable to effect changes to the patriarchal socio-political status quo. This article studies the Saudi woman life writer Manal al-Sharif’s Daring to Drive (2017) to demonstrate the various ways in which the subjugated women instigate social transformations by resisting against the prevailing male dominated system. To this end, Michel Foucault’s theories on “other spaces” are employed to examine the function of spatial modalities in the workings of the dynamics of power. It is argued that the portrayed female subjects re-construct, re-experience and re-utilise different spaces to re-invent new identities and galvanise alternative ways of life. The analysis reveals that within the emancipatory space of the Internet, Saudi women produce heterotopias of transgressions, resistance and utopianism to unsettle the prescribed boundaries of male-female relations, protest against the impositions of gender performance in public spheres and creatively re-imagine an alternative, desirable order of things. Hence, the study arrives at two conclusions: first, Saudi women’s individual urgency for self-transformation have generated major social changes and ideological reconfigurations, resulting in many of the recent democratic developments in the country; second, space is not merely a normalised and rationalised construct, but can function as a normalising and transformative force at the same time.